Nevan, Lisa and Richard Kendall. - Sahl, Ted (photographer):::Creator::::::::::::
Unknown individuals gathered at a table. Known individuals are Nevan, standing in the back wearing suspenders, Lisa sitting next to Nevan and Richard Kendall, sitting on the left hand side, fourth from left.